Analisis Penerapan Standar Akuntansi Keuangan UMKM pada Pelaku Usaha Pariwisata Berbasis Desa Wisata di Desa Adat Osing Kemiren Kabupaten Banyuwangi - Maulana, Jeki Brian; Siswanto, Adil (Lembaga Teewan Journal Solutions, 2026)
This study aims to analyze the implementation of the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) among MSME actors in Osing Adat Kemiren Tourism Village. MSMEs in tourism villages play a strategic role in supporting tourism activities and improving the local economy. However, in practice, many MSME actors have not yet prepared financial records and financial statements in accordance with applicable accounting standards. This research uses a qualitative method with a descriptive approach. Data collection techniques include interviews, observation, and documentation involving MSME actors and the village tourism management. Data analysis is conducted systematically to describe the actual conditions regarding the implementation of SAK EMKM. The results show that most MSMEs in Osing Adat Kemiren Tourism Village have not fully implemented SAK EMKM in their financial management. This is due to limited knowledge, lack of understanding of accounting standards, and minimal training and assistance. Nevertheless, some MSMEs have carried out simple financial recording as an initial step toward accounting implementation. Therefore, continuous efforts are needed through socialization, training, and mentoring programs to improve MSME capacity in implementing SAK EMKM optimally, so that the quality of financial reporting can be enhanced and business development can be sustained.